RESPON PESERTA DIDIK TERHADAP PENGGUNAAN MODEL CHILDREN LEARNING IN SCIENCE TENTANG USAHA DAN ENERGI - Indah Sanita Dirsa; Haratua Tiur Maria S; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to know the response of  junior high school students grade VIII at using of the Children Learning In Science (CLIS) model. The method used in this study is an eksperimental method in the form of survey. Sample of this study chossesed with  the purposive sampling method so that class VIII A was selected in SMP Negeri 6 Sambas. The data collection techniques in the form of a questionnaire response. The response questionnaire in this study consisted of 5 aspects with 6 negative statements and 6 negative statements. The statement is used to know students 'responses to the use of CLIS models in improv students' critical thinking skills. Subjects in this study were 28 students. Based on the results of research conducted, it can be concluded that the analysis of the questionnaire responses of students gave a positive response to the CLIS model used to improve critical thinking skills  a matter of work and energy showed a response of 72% with a high category. The response questionnaire can be used as a benchmark to find out the improvement of critical thinking skills by using the CLIS model a matter of work and energy Keywords:  CLIS , Respon,  Work and Energy